Analyzing the effect of instruction based on classroom assessment techniques in prospective teachers’ achievement - (:unkn) unknown (Kamla-Raj Enterprises, 2015)
The purpose of this study is to investigate the effect of the implementation of an instructional process using Classroom Assessment Techniques (CAT) on student teachers’ understanding of the instructional methods presented in the Instructional Principles and Methods course, which is taught in educational faculties. Moreover, it aims to determine whether using CAT while teaching contributes positively to students’ learning as measured by students’ feedback. The study was designed using a mixed method approach. Pre-test results suggested no significant difference between the learning levels of students in the experimental group and students in the control group. At the end of the teaching process, student achievement levels in both groups demonstrated significant progress. A comparison between post-test scores revealed that students in the experimental group had significantly better scores than those in the control group. 38 students in the experimental group stated that instruction with CAT made a positive contribution to their learning. © Kamla-Raj 2015.
Keywords: Assessment techniques; Instruction; Learner’s Achievement